Business travellers' choice of airlines at Kuching International Airport, Sarawak - Chuo, Hock Tieng (Universiti Malaysia Sarawak, (UNIMAS), 2012)
([his paper aims to determine the effect of demographic on type of airlines chosen, the effect of company size on the choices of airlines and consideration taken by business travellers before choosing which airlines to fly. The result reveals some dissimilarity compared to previous works done. Business travellers in this study consist largely of young and energetic traveller aged below 35 years old It is found that there are greater number of women travellers than previous studies on both Full Service Carrier (FSC) and Low Cost Carrier (LCC). Sales and service visits are the main purpose of travel for Kuching business travellers. Generally, the travellers booked the ticket themselves. Internet site is the most popular for business traveller who travels on Air Asia while traditional travel agent remains old time favourite for business traveller travelling on Malaysia Airlines. Online purchasing of tickets for FSC passenger is in the increasing trend. Company size does not seem to playas important role in type of carrier chosen as traditionally observed in more develop and liberal market. Smaller companies do use the FSC for business purposes. FSC travellers are mostly coming from company with travel policy but most of the companies encourage the LCC usage. Punctuality and flight frequency/schedule were rated the most important attribute while business lounge were the least important to business travellers for both FSC and LCe. This study reveals early sign of more liberal market. Competition would literally heat up and mature the market to higher level provided less government intervention, which may lead to unfair competition.